Morphodynamics of River Deltas in Response to Different Basin Water Depths: An Experimental Examination of the Grade Index Model. Issue 10 (20th May 2019) - Wang, Junhui; Muto, Tetsuji; Urata, Kento; Sato, Toshihiko; Naruse, Hajime
Abstract: Basin water depth ( h ) governs the long‐term morphodynamics of river deltas, which are embodied in the grade index ( G index ). The G index, a volume‐in‐unit‐time ratio of subaerial sediment allocation to the entire supplied sediment, can be given as a function of the dimensionless basin water depth ( h * ). Tank experiments reported herein reveal that delta progradation and deltaplain aggradation are suppressed and distributary channel migration and avulsion take place less frequently when the G index value is lower (i.e., when the basin water is deeper; h *  ≫ 1). If the G index ~0 (i.e., extremely deep basin water; h * ~+∞), the delta can neither prograde nor aggrade, and the distributary channels tend to stabilize. The grade index model helps explain the contrasting morphodynamics of the Liwu Delta (east Taiwan) and Yellow River Delta, as natural examples of deepwater and shallow‐water deltas, respectively. Plain Language Summary: It has long been known that the behavior of river deltas is controlled by upstream conditions, such as variations in sediment and water discharges, which reflect the geology, climate, and tectonics of the hinterlands. Recent research suggests that the basin water depth as a downstream condition can also govern delta morphodynamics, although it is often overlooked. Evidence suggests that channels tend to be more stable on deltas that face deeper water basins and more prone to avulse in the opposite case. To date, models that provide a theoretical explanation for these phenomena are rare. To explore this explanation, a series of tank experimental runs was conducted. The results of the experiment confirm that deeper basin water suppresses delta progradation and causes less sediment to be distributed subaerially, which is accompanied by slower channel bed aggradation and more‐stabilized channels. Such a process can be quantitatively described by the grade index model, which is applicable to natural deltas and might help in the evaluation of the stability of delta distributary channels. Key Points: The rationale that basin water depth ( h ) can stabilize delta distributary channels is experimentally confirmed A larger h tends to yield a lower G index, which suppresses delta progradation and aggradation, channel migration, and avulsion The grade index model might explain and predict the long‐term morphodynamics of natural river deltas in different bathymetric settings